Pipeline Embolization Device for Treatment of Extracranial Internal Carotid Artery Pseudoaneurysms: A Multicenter Evaluation of Safety and Efficacy. (18th December 2021) - Akinduro, Oluwaseun O; Gopal, Neethu; Hasan, Tasneem F; Nourollah-Zadeh, Emad; Vakharia, Kunal; De Leacy, Reade; Burkhardt, Jan-Karl; Yamamoto, Junichi; Mocco, J; Castilla, Leonardo Rangel; Kan, Peter Tze Man; Boulos, Alan; et al.
Graphical Abstract: